2020
DOI: 10.3390/ijms21176293
|View full text |Cite
|
Sign up to set email alerts
|

Sleep as a Novel Biomarker and a Promising Therapeutic Target for Cerebral Small Vessel Disease: A Review Focusing on Alzheimer’s Disease and the Blood-Brain Barrier

Abstract: Cerebral small vessel disease (CSVD) is a leading cause of cognitive decline in elderly people and development of Alzheimer’s disease (AD). Blood–brain barrier (BBB) leakage is a key pathophysiological mechanism of amyloidal CSVD. Sleep plays a crucial role in keeping health of the central nervous system and in resistance to CSVD. The deficit of sleep contributes to accumulation of metabolites and toxins such as beta-amyloid in the brain and can lead to BBB disruption. Currently, sleep is considered as an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 139 publications
(188 reference statements)
1
57
0
Order By: Relevance
“…In recent years, sleep disorders are linked to Alzheimer's disease progression in addition to the typical symptoms of progressive loss of memory, speech and cognition 12,13 . A high prevalence (25-66%) of Alzheimer's disease patients was reported to exhibit various types of sleep disorders, including excessive daytime sleepiness (EDS), sundowning, nocturnal wandering, sunset syndrome, sleep breathing disorder (SBD) and insomnia 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, sleep disorders are linked to Alzheimer's disease progression in addition to the typical symptoms of progressive loss of memory, speech and cognition 12,13 . A high prevalence (25-66%) of Alzheimer's disease patients was reported to exhibit various types of sleep disorders, including excessive daytime sleepiness (EDS), sundowning, nocturnal wandering, sunset syndrome, sleep breathing disorder (SBD) and insomnia 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Further studies of this hypothesis will shed light on the mechanisms by which Aβ is cleared from the brain. In our recent review, we discussed that the EEG dynamics can be a potential biomarker of BBB integrity [25]. Here we propose the EDFA analysis of EEG data and show that OBBB can be identified based on the EEG data using long-range power-law correlations.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, it has been discussed that the electroencephalographic (EEG) dynamics can be a potential biomarker of BBB integrity [25]. In our preliminary studies, we were demonstrated the successful application of nonlinear analysis of EEG patterns in the evaluation of OBBB [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The PS-lymphatic therapy can be important also for silent SAH and subdural hemorrhages, which are located superficially and are identified in 46-50% of mature babies [52]. Our data are limited by the study of one protocol of PS influences on the lymphatic evacuation of RBCs, while it has actively discussed that sleep can be a natural factor of activation of the lymphatic functions in the brain [53]. We assume that PS application during deep sleep can significantly enhances therapeutic effects of PS on brain bleedings and causes more pronounced influences on regenerative lymphatic mechanisms.…”
Section: Discussionmentioning
confidence: 99%